A phenomenological approach to the collaborative consumer. Issue 6 (31st May 2019) - Barbosa, Belem; Fonseca, Isabel
Abstract : Purpose: Collaborative consumption emerges from social practices such as sharing, lending and gifting. It is becoming more common among consumers, boosted by the internet, which facilitates the collaboration process with both strong and weak ties. This paper aims to examine collaborative consumer experience, delving into the factors that contribute to the adoption and the perceived benefits of this alternative form of consumption. Design/methodology/approach: A total of 12 phenomenological interviews were conducted o explore the theme from an individual perspective, attested by the consumers' narratives and experiences. Findings: The results highlight collaborative consumption as being influenced by family practices, social relations and the current economic scenario. Also, noteworthy is the evidence that collaborative consumption enables consumers to select from a more diversified portfolio of products and services, especially the ones featured by the internet and social media. Consumers perceive financial, emotional, social, environmental and increased consumption benefits, depending on their practices of collaborative consumption, and also on their role as providers, consumers or exchangers. Originality/value: Through the phenomenological approach, based on individual reports of experiences related to collaborative consumption, it was possible to highlight some aspects relevant to better understanding the behavior of collaborative consumers.